NARASI HISTORIS PEMIKIRAN PENDIDIKAN ISLAM TENTANG ANAK: RELEVANSI SOSIAL-KULTURAL BAGI PAUD ISLAM INDONESIA - Kurnia, Asraf; Samad, Duski; Mamad, Firdaus Sutan; Matanari, Thamara Putriani Br; Enjoni (LPPM IAD Probolinggo, 2025)
Classical Islamic educational thought holds valuable principles relevant to early childhood education, particularly within Islamic Early Childhood Education (PAUD) institutions in Indonesia. However, modern educational systems often overlook the historical contribution of Islamic thought in shaping children’s character. This study aims to explore the historical narrative of Islamic educational thought on children and analyze its relevance to current PAUD practices. This research adopts a qualitative approach using historical and content analysis methods. Data sources include the works of Al-Ghazali, Ibn Sina, and Ibn Khaldun, as well as contemporary literature on Islamic PAUD practices. The findings indicate that values such as adab, ruhiyah, compassion, and social responsibility remain highly relevant and can be contextually integrated into Islamic PAUD curricula. The study recommends revitalizing classical Islamic educational values in the development of PAUD curricula and pedagogical strategies rooted in Islamic character and spirituality. Keywords: classical Islamic education; early childhood; Islamic PAUD; adab values; educational history